2013
DOI: 10.1088/0029-5515/53/11/113006
|View full text |Cite
|
Sign up to set email alerts
|

How is turbulence intensity determined by macroscopic variables in a toroidal plasma?

Abstract: We report observations of the dynamic response of micro-fluctuations and turbulent flux to a low-frequency heating power modulation in the Large Helical Device. The responses of heat flux and micro-fluctuation intensity differ from that of the change in temperature gradient. This result violates the local transport model, where turbulence is determined by the local temperature gradient. A new relationship between flux, gradient and turbulence is found. In addition to the temperature gradient, the heating rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
125
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(135 citation statements)
references
References 36 publications
8
125
1
1
Order By: Relevance
“…In addition, the studies of relation between heat/particle/momentum flux and temperature/density/flow gradient are shown that the flux is not necessarily determined by the local plasma parameters. [10][11][12][13][14][15][16][17] In cold pulse propagation experiments, for example, the core plasma temperature shows the fast change after the edge cooling. [18][19][20] The change of temperature is much faster than the expected value from the diffusive process in a thermal transport.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the studies of relation between heat/particle/momentum flux and temperature/density/flow gradient are shown that the flux is not necessarily determined by the local plasma parameters. [10][11][12][13][14][15][16][17] In cold pulse propagation experiments, for example, the core plasma temperature shows the fast change after the edge cooling. [18][19][20] The change of temperature is much faster than the expected value from the diffusive process in a thermal transport.…”
Section: Introductionmentioning
confidence: 99%
“…This new method directly measures the gradient-flux relation by studying the temperature response with respect to modulations of the electron cyclotron heating (ECH) power. Using this method, hysteresis in the gradient-flux relation was observed in LHD plasmas [1,2]. Because heat flux is a multivalued function of gradient, the temperature perturbation dynamics are far from a simple diffusive response with constant diffusion coefficient.…”
mentioning
confidence: 99%
“…We apply the telegraph equation to the heat pulse propagation caused by periodic modulation of the heating power. The result is compared qualitatively with that from an LHD experiment [1]. However, the model cannot explain the phase relation in the hysteresis between the temperature gradient and the heat flux.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, limitations have been recognized in conventional diffusive models of transport, which employ Fick's law to relate the temperature gradient and heat flux [1,2]. In electron cyclotron heating (ECH) power modulation experiments in the large helical device (LHD), turbulent flux is changed before changes in local gradients occur [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation